Quasi-Distributed Torque and Displacement Sensing on a Series Elastic Actuator's Spring Using FBG Arrays Inscribed in CYTOP Fibers - Marques, Carlos; Kalli, Kyriacos; Siqueira, Adriano A.G.; Min, Rui; Frizera, Anselmo; Theodosiou, Antreas; Casas, Jonathan; Leal-Junior, Arnaldo G.; Pontes, Maria José; Dos Santos, Wilian M.; Diaz, Camilo R. (My University, 2019)
We report the application of fiber Bragg grating (FBG) arrays in polymer optical fibers for the quasi-distributed displacement and torque sensing in a series elastic actuator's spring. The arrays were inscribed in cyclic transparent optical polymer fiber through the direct-write, plane-by-plane inscription method using a femtosecond laser. Two arrays with four FBGs each were positioned on a rotary spring, and a numerical analysis using the finite-element method was performed to evaluate the sensors' behavior under different loading conditions. Experimental tests were performed on the spring, and the results show that the FBGs responses follow the predicted numerical simulations. In addition, a Kalman filter was applied on the response of the FBGs for sensor fusion, leading to a more accurate torque estimation, where the relative error for the torque estimation was improved by a factor of 7. Furthermore, transverse forces were applied on the predefined points of the spring in order to show the ability of the quasi-distributed sensor approach to identify external mechanical disturbances on the spring.
Keywords: Fiber Bragg gratings; Kalman filter; Polymer optical fiber; Series elastic actuators; Torque sensor